THE CASE OF NEJVETSI Z PIEROTU BY FRANTISEK KOZIK - Lukas, Martin (Bohemica Olomucensia, 2021)
The paper is a case study on popular Czech biographical novel Nejvetsi z Pierotu by Frantisek Kozik published in 1939. After a concise context overview and a brief characterization of the novel, the study focuses on how the novel was received by the critics and what promotional strategy its publisher adopted, showing what was and what was not considered literary value in the Protectorate of Bohemia and Moravia.
Keywords: Nejvetsi z Pierotu; Jean Gaspard Deburau; Frantisek Kozik; Czech biographical novel; polemic